Current challenges in the management of sepsis in ICUs in resource–poor settings and suggestions for the future - Thwaites, C; Schultz, M; Dunser, M; Dondorp, A; Adhikari, N; Iyer, S; Kwizera, A; Lubell, Y; Papali, A; Pisani, L; Riviello, B; Angus, D; et al. (Springer, 2017)
Sepsis is a major reason for intensive care unit (ICU) admission, also in resource–poor settings. ICUs in low– and middle–income countries (LMICs) face many challenges that could affect patient outcome. The aim of this review is to describe differences between resource–poor and resource–rich settings regarding the epidemiology, pathophysiology, economics and research aspects of sepsis. We restricted this manuscript to the ICU setting even knowing that many sepsis patients in LMICs are treated outside an ICU. Although many bacterial pathogens causing sepsis in LMICs are similar to those in high–income countries, resistance patterns to antimicrobial drugs can be very different; in addition, causes of sepsis in LMICs often include tropical diseases in which direct damaging effects of pathogens and their products can sometimes be more important than the response of the host. There are substantial and persisting differences in ICU capacities around the world; not surprisingly the lowest capacities are found in LMICs, but with important heterogeneity within individual LMICs. Although many aspects of sepsis management developed in rich countries are applicable in LMICs, implementation requires strong consideration of cost implications and the important differences in resources. Addressing both disease–specific and setting–specific factors is important to improve performance of ICUs in LMICs. Although critical care for severe sepsis is likely cost–effective in LMIC setting, more detailed evaluation at both at a macro– and micro–economy level is necessary. Sepsis management in resource–limited settings is a largely unexplored frontier with important opportunities for research, training, and other initiatives for improvement.